Emotional framing in online environmental activism: Pairing a Twitter study with an offline experiment - Sanford, Mary; Witkowska, Marta; Gifford, Robert; Formanowicz, Magda (Frontiers in Psychology, 2023)
As the consequences of anthropogenic climate change become more apparent, social media has become a central tool for environmental activists to raise awareness and to mobilise society. In two studies, we examine how the emotional framing of messages posted by environmental activists influences engagement and behavioural intentions towards environmental action. In the first study, tweets (N = 510k) of fifty environmental activists posted between November 2015 and December 2020 are examined to measure their emotional content and its relation to tweet diffusion. Environment-related tweets are found to be shared more the less they contain positive emotion and the more they contain negative emotion. This result supports the negativity bias on social media. In Study 2 (N = 200), we experimentally test whether negatively versus positively framed environmental content leads to increased reported intent to engage with collective action, and whether mood mediates that link. We find both direct and indirect effects on reported climate action intentions when mood is used as a mediator. The negative mood resulting from seeing negative tweets makes participants more likely to report higher action intention (indirect effect) - congruent with Study 1. However, seeing negative tweets also makes participants less inclined to act (direct effect), indicating a suppression effect and the presence of other factors at work on the pathway between information and action intent formation. This work highlights the complex and multifaceted nature of this relation and motivates more experimental work to identify other relevant factors, as well as how they relate to one another.